Impact of transparency on foreign direct investment (FDI) inflows and FDI- growth link in European countries - Salihu, Shuaibu (2019)
The role of foreign direct investment (FDI) inflows in the host country cannot be overemphasized and therefore, creating the transparent business environment is equally important in attracting FDI inflows into the recipient economy. Thus, this will mitigate investment risks such as corruption, risk of expropriation and inefficient bureaucracy. Besides the traditional factors that affect FDI inflows (e.g market size, infrastructure, labour, etc), there has been a shift in paradigm towards the non-traditional factors in last two decades, such as policy changes by the host country which is characterized by transparent formulation and implementation motivated this research which are vital in attracting FDI inflows. This study examines the impact of transparency on FDI inflows and FDI-growth link in European countries. The Dynamic Panel Quantile Regression with non-additive fixed effect is employed to achieve the objectives of the study on the panel of 41 countries from the period of 1998 through 2016. The empirical findings suggest that transparency has a positive impact on FDI inflows in European countries and statistically significant. In addition, the empirical findings demonstrate that the robustness is evidenced with alternative measure of transparency index (institutional quality indicator) and the splitting of the sample countries based on income levels. The finding reveals that the effect of transparency on FDI inflows is more in uppermiddle- income economies than high-income economies in Europe. Besides, the moderating impact of FDI inflows on economic growth through transparency is positive and significant and the marginal effect is equally positive and significant at minimum, mean and maximum levels. However, the magnitude of FDI on economic performance at the maximum due to changes in transparency is quite higher than the mean and minimum level across the estimated quantiles. The policy maker (government) should formulate and implement policies that will promote and guarantee transparent business environment such as decline in corruption level, efficient and sound bureaucracy, rule of law that are blind, absence of repudiation of contracts and expropriation of property. With these in place, such economy will serve as an attractive destination of the inflows of FDI and which the spillover effects will ultimately enhance economic growth.